The interaction of phages and bacteria: the co-evolutionary arms race. (17th February 2020) - Safari, Fatemeh; Sharifi, Mehrdad; Farajnia, Safar; Akbari, Bahman; Karimi Baba Ahmadi, Mohammad; Negahdaripour, Manica; Ghasemi, Younes
Abstract: Since the dawn of life, bacteria and phages are locked in a constant battle and both are perpetually changing their tactics to overcome each other. Bacteria use various strategies to overcome the invading phages, including adsorption inhibition, restriction–modification (R/E) systems, CRISPR–Cas (clustered regularly interspaced short palindromic repeats–CRISPR-associated proteins) systems, abortive infection (Abi), etc. To counteract, phages employ intelligent tactics for the nullification of bacterial defense systems, such as accessing host receptors, evading R/E systems, and anti-CRISPR proteins. Intense knowledge about the details of these defense pathways is the basis for their broad utilities in various fields of research from microbiology to biotechnology. Hence, in this review, we discuss some strategies used by bacteria to inhibit phage infections as well as phage tactics to circumvent bacterial defense systems. In addition, the application of these strategies will be described as a lesson learned from bacteria and phage combats. The ecological factors that affect the evolution of bacterial immune systems is the other issue represented in this review.